Brown Sugarcane as The Forthcoming Innovation for Athlete’s Sports Food Product: A Narrative Review - Solichah, Kurnia Maratus (Universitas Ahmad Dahlan, 2024)
Brown sugarcane is widely known as an additional sweetener in cuisines and beverages. Brown sugarcane has higher contents of carbohydrates, fats, and proteins than brown coconut or palm sap sugar. Athletes usually consume such food before, during, and after a match to restore nutrients. It also benefits as reserves during endurance sports because carbohydrate content can be used to supply energy during the long duration of competition. Simple carbohydrates in brown sugar cane are known to be able to increase blood glucose gradually. This condition provides good benefits for athletes, because the energy source reserves can be stored longer and fatigue can be delayed. Diverse sports food products, such as sports drinks, gels, or bars, could be developed from brown sugarcane. Additional materials are adjusted to the sport of developed food and beverage. Notwithstanding, studies regarding the product development and metabolic effect of brown sugarcane supplementary are needed, particularly during exercise.